International Guarantees of Foreign Investment Protection - A. M. Ibragimov (Московский журнал международного права, 2011)
In the scientific article on the bases of normative and other material study the author analyzes international guarantees of foreign investment protection. The analysis of sources of these guarantees showed that the foreign investments are under regulated influence not only of public but also private law. At that granting law guarantees to the direct foreign investments is basically a private law act in content but in form it can be realized in the international public legal status.In the article the author pays special attention to the intrastate legal acts corresponding to the international law documents that is in point of fact appear a key factor of the foreign investments goal.